Advancing Elementary Education: A Personalized e-Math Approach Using Interactive Gamification - Wati, Unik Ambar; Nurlayli, Akhsin; D, Siti Irine Astuti; Murrti, Rahayu Condro; Kurniawan, Hendra Listya; Fitriya, Yeni; Ramadhani, Deasy (Journal of Education Reseach and Evaluation, 2025)
PISA's assessment criteria aim to gauge the efficacy of educational systems in equipping students with the skills to utilize mathematical knowledge across various life aspects, thereby nurturing them into constructive, engaged, and reflective citizens for the 21st century. Our research focus is on scrutinizing the current spectrum of research and advancements relevant to the integration of e-learning, gamification, and personalized learning methodologies within elementary mathematics education. The Game Development Life Cycle process encompasses an iterative methodology with six distinct phases: Initiation, Pre-Production, Production, Testing, Beta, and Release. The beta testing phase, which involved 265 respondents, was conducted using the System Usability Scale (SUS) to assess the usability of the new software. The SUS, a proven and efficient tool, consists of a 10-item questionnaire that gauge’s users' overall satisfaction with the product.  This result serves as a valuable feedback mechanism, guiding the development team on where to focus their efforts in refining the software's interface and functionality to enhance the overall user experience in subsequent iterations. The integration of e-learning, personalization, and gamification in elementary mathematics education offers promising benefits in terms of accessibility, engagement, and learning outcomes. However, challenges such as the digital divide and the need for teacher training must be addressed to maximize their potential. The presented game development methodology serves as a structured guide for creating effective personalized educational games, contributing to the ongoing discourse on innovative approaches to mathematics education.